Potential Impacts of Fukushima Nuclear Leakage on China’s Carbon Neutrality—an Investigation on Nuclear Power Avoidance and Regional Heterogeneity - Li, Chengyu; Yan, Xiangwu; Liu, Baoquan; Yang, Zhenbing; Zhou, Li (Frontiers in Environmental Science, 2021)
Fukushima nuclear accident delayed the process of China's nuclear power construction and may have a certain potential impact on goal of carbon neutrality by 2060. Based on the idea of a quasi-natural experiment, this paper collected the carbon emissions data of 30 provinces and cities in China from 2000 to 2017, and explored the accident impact and mechanism on carbon emissions in the provinces with nuclear power. The results showed that this leakage had different impacts on China's nuclear power provinces. Due to the large proportion of manufacturing industry and high dependence on energy, the carbon emissions in Jiangsu rose after impacted by the incident, in contrast, the research results in Guangdong and Zhejiang were opposite. Through the mechanism test, it was found that the incident impact had reduced the carbon emissions of Guangdong and Zhejiang by improving the industrial structure and energy efficiency, with the explanation ratios of 10.45% and 15.1% respectively. Technological innovation had obscured the emission reduction effect of the incident impact, and the innovation driving force for green development in nuclear power base provinces was insufficient. These findings are helpful to analyze the regional layout of China's nuclear power and have implications for carbon neutrality.